Farmer Field Schools on Sustainable Management of Clumping Bamboo Facilitators Manual: Part 2 - Klein, C.H. de; Spuij, M.; Durai, J. (International Bamboo and Rattan Organisation (INBAR), 2021)
This manual provides guidelines for initiation of bamboo Farmers Field School (FFS) groups, and for facilitation of these groups. The manual is intended for both FFS facilitators, who are charged with the day-to-day responsibilities to facilitate the FFS groups, and for the FFS coordinators, who are charged with selection and supervision of the FFS facilitators.